Penerapan Media Video dalam Pembelajaran Teks Hikayat Kelas X SMAN 11 Semarang - Nur Hamida, Salma Salshabella; Asropah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
The aim of this research is to analyze the application of video media in teaching saga texts for class X SMA. The research method is qualitative, while the data analysis steps include firstly data collection, secondly data reduction, thirdly data presentation, and fourthly drawing conclusions. The results of the research include the first application of video media in learning saga texts carried out in three stages, namely the preparation stage starting with the researcher seeing directly the process of learning the saga text material, the implementation stage here includes preliminary, content and closing activities and reflection is a process to find out learning success, the intended success is the success of students understanding of the material being studied. The second evaluation of video media in learning saga texts showed that more students had higher KKM scores when learning was implemented using video media. The three obstacles include external obstacles, including limited time and internal obstacles, including the existence of students who are not yet motivated to participate in learning seriously.